2018
DOI: 10.1039/c8ta07627h
|View full text |Cite
|
Sign up to set email alerts
|

All-porous heterostructure of reduced graphene oxide–polypyrrole–nanoporous gold for a planar flexible supercapacitor showing outstanding volumetric capacitance and energy density

Abstract: We propose a new prototype of flexible planar supercapacitor with highly conductive all-porous morphology of all the electroactive layers that shows outstanding volumetric stack capacitance (245.34 F cm−3) and energy density (98.48 mW h cm−3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 63 publications
2
35
0
Order By: Relevance
“…The obtained results demonstrate that the capacitance properties of GO-modified PPy coatings could be easily improved without it being necessary to employ other nanoparticles, complex architectures, or harmful reagents [6,16,33,[41][42][43]. Despite the fact that the varying test parameters allowed only a qualitative comparison with the literature, it was observed that the performance of the obtained thin hybrid PPy/rGO coatings was similar to other reports [41].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The obtained results demonstrate that the capacitance properties of GO-modified PPy coatings could be easily improved without it being necessary to employ other nanoparticles, complex architectures, or harmful reagents [6,16,33,[41][42][43]. Despite the fact that the varying test parameters allowed only a qualitative comparison with the literature, it was observed that the performance of the obtained thin hybrid PPy/rGO coatings was similar to other reports [41].…”
Section: Discussionsupporting
confidence: 81%
“…The obtained results demonstrate that the capacitance properties of GO-modified PPy coatings could be easily improved without it being necessary to employ other nanoparticles, complex architectures, or harmful reagents [6,16,33,[41][42][43]. Despite the fact that the varying test parameters allowed only a qualitative comparison with the literature, it was observed that the performance of the obtained thin hybrid PPy/rGO coatings was similar to other reports [41]. The benefits of the present work consist of the improvement of the capacitance properties by simply adjusting the electrochemical parameters while using less added GO, thanks to the use of an anionic surfactant to better disperse the GO sheets and enhance their reactivity.…”
Section: Discussionmentioning
confidence: 78%
“…Among the various electrodes, flexible and porous electrodes not only provide an interconnected network as electron and ion pathways for efficient charge and mass exchange during faradic redox reactions, but also allow more electroactive sites to be exposed to the electrolyte . Although many three‐dimensional (3D) electrode architectures have been developed, such as carbon nanotube sponges, graphene aerogels, metal foams, and polymer hydrogels, there are still many issues to be addressed: 1) carbon nanotube sponges and graphene aerogels are difficult to be produced in large scale because of their relatively high cost and/or complex preparation processes; 2) carbon foams are usually less conductive as compared to metals; 3) rigid electrodes with metals as current collectors cause their devices less flexible; and 4) most 3D electrodes possess structures with single macropores, which could form ion‐buffering reservoirs and accelerate ion transport, but contribute little to the large surface area for depositing electroactive substances, thus resulting in relatively low capacitances . Therefore, it is imperative to develop novel 3D electrodes with hierarchical pores, high conductivity, good flexibility, and easy fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a hybrid graphite flake/PPy electrode MSC showed a capacitance of 6 mFcm −2 . Hybrid rGO/PPy was deposited on NPG to form a 3D heterstructure with high conductivity, and the fabricated flexible MSC showed an area capacitance of 29.21 mFcm −2 with an unprecedented energy density of 98.48 mWhcm −3 …”
Section: Materials For Msc Electrodesmentioning
confidence: 99%